Transformasi Kurikulum PAUD Berbasis Musik Multisensori untuk Penguatan Nasionalisme Anak Usia Dini - Siti Khoiriyah; Heriestia Salma Rizky Khairani; Fetty Ernawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The Early Childhood Education (PAUD) curriculum plays an important role in shaping young children’s learning experiences. However, in practice, there are still several challenges, such as a lack of meaningful learning and the suboptimal integration of nationalism values. Therefore, curriculum innovation is needed to incorporate approaches that align with children’s characteristics.This study aims to analyze and develop the concept of transforming the PAUD curriculum based on a multisensory music approach as an effort to strengthen nationalism values in early childhood. The method used is a library research approach by reviewing various sources, including scientific journals, books, and relevant previous studies. The data analysis technique is conducted descriptively and qualitatively through processes of organizing, categorizing, and interpreting data.The results of the study indicate that a multisensory music-based approach can enhance children’s engagement, participation, and understanding in learning. The integration of audio, visual, and kinesthetic elements has proven effective in stimulating children’s motor, cognitive, and affective development. In addition, the use of audio-visual media helps children understand nationalism values in a more concrete and meaningful way.In conclusion, transforming the PAUD curriculum through a multisensory music-based approach is an effective strategy to create enjoyable and holistic learning experiences while strengthening the internalization of nationalism values from an early age.